Synergetic Coupling of Lithiophilic Sites and Conductive Scaffolds for Dendrite‐Free Lithium Metal Anodes. Issue 6 (24th April 2019) - Chen, Xiao‐Ru; Li, Bo‐Quan; Zhao, Chang‐Xin; Zhang, Rui; Zhang, Qiang
Abstract: Lithium metal is highly considered as an ideal anode material because of its ultrahigh theoretical capacity of 3680 mA h g −1 and the lowest potential of −3.04 V versus the standard hydrogen electrode. However, uncontrollable lithium dendrite growth severely impedes the practical applications of lithium metal batteries. The introduction of a lithium host is an effective strategy to inhibit lithium dendrite growth, where lithiophilicity and conductivity of the lithium host play the dominant role. In this contribution, the synergistic effect of lithiophilic sites and conductive scaffolds is investigated to construct an optimized lithium host for dendrite‐free lithium metal anodes. Consequently, the lithium host with balanced lithiophilicity and conductivity demonstrates excellent electrochemical performances regarding to high Coulombic efficiency of 98% stable for 300 cycles at 1.0 mA cm −2 and improved capacity retention of 86.2% after 100 cycles in LiFePO4 full cells. The synergistic coupling of lithiophilicity and conductivity of lithium hosts enhances the understanding of lithiophilic chemistry to achieve next‐generation high‐performance batteries. Abstract : Synergistic coupling of lithiophilic sites and conductive scaffolds is proposed as a rational strategy to construct desirable Li hosts for dendrite‐free Li metal anodes. The optimized Li hosts with balanced lithiophilicity and conductivity afford lower Li nucleation overpotentials, faster kinetics, and excellent electrochemical performances for better understanding of lithiophilic chemistry.